Information Inequality With Insider Trading Practices in The Indonesian Capital Market - Nararia Aji Bhuana; Celia Rahma Putri Eritika; Brawijaya B Kusuma (Syiah Kuala Law Journal, 2021)
This paper focus on discussing the issue of insider trading pratices in the Indonesian capital market. Bearing Act 8 of 1995 concerning the Capital Market does not provide a clear definition of insider trading. Insider trading is a practice carried out by people in the corporation who in carrying out trading activities make use of information exclusively through insiders. Insider trading is one of the crimes in the capital market which has a very detrimental impact on many parties. The existence of inside information that is not yet available to the public is misused to trade shares on that information. The practice of insider trading is a capital market crime which in terms of proof is very difficult to prove. The practice of insider trading is a violation of the principle of transparency, even though the objective of implementing the principle of openness is to ensure transparency in capital market activities.